2020
DOI: 10.1029/2020gl089065
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclones Significantly Alleviate Mega‐Deltaic Erosion Induced by High Riverine Flow

Abstract: The drastic decline in sediment discharge experienced by large rivers in recent years might trigger erosion thus increasing the vulnerability of their extensive deltas. However, scarce information is available on the erosion patterns in mega-deltas and associated physical drivers. Here a series of bathymetries in the South Passage, Changjiang Delta, were analyzed to identify morphodynamic variations during high riverine flow and tropical cyclones (TCs). Results indicate that high river flow during flood season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…Elsewhere in the world, much of the research around marine storm impacts to marshes has focused on major river systems experiencing extreme human modifications and tropical cyclone‐induced flood events. For example, in the Mississippi River and Changjiang Deltas, studies have found that the modern decline in riverine sediment inputs caused by dams and levees has been partially counteracted by marine sediment mobilized and delivered by waves and surge during tropical cyclones (Sanks et al., 2020; Smith et al., 2015; Wang et al., 2020). Our findings are therefore complementary to those along these major river systems in that we provide insight into another endmember: small estuaries impacted by more frequent and less intense extratropical storms.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere in the world, much of the research around marine storm impacts to marshes has focused on major river systems experiencing extreme human modifications and tropical cyclone‐induced flood events. For example, in the Mississippi River and Changjiang Deltas, studies have found that the modern decline in riverine sediment inputs caused by dams and levees has been partially counteracted by marine sediment mobilized and delivered by waves and surge during tropical cyclones (Sanks et al., 2020; Smith et al., 2015; Wang et al., 2020). Our findings are therefore complementary to those along these major river systems in that we provide insight into another endmember: small estuaries impacted by more frequent and less intense extratropical storms.…”
Section: Discussionmentioning
confidence: 99%
“…The Nanhui tidal flat is located in the Nanhui Shoal which lies in the southern margin of the Yangtze Delta, China. The Nanhui Shoal is adjacent to the South Passage and is the fastest growing area in the delta, benefitting from previous abundant sediments transported into the subaqueous delta (Dai et al, 2015;Fan et al, 2017;Wang et al, 2020;Fig. 1B).…”
Section: Nanhui Tidal Flatmentioning
confidence: 99%
“…The offshore inputs into the Yangtze River mouth have been reported in many previous studies (e.g., Du et al, 2010;Ge et al, 2020;Wang et al, 2021) and surficial sediments in the subaqueous delta have yielded OSL ages exceeding 1,000 a (e.g., core A5-4 in Cheng et al, 2020; see Figure 1B for the core location). When older sediments are imported into the river mouth by processes such as tidal pumping, estuarine circulation induced by saltwater intrusion, and storm events (Warner et al, 2008;Cho et al, 2012;Li et al, 2016;Burchard et al, 2018;Wang et al, 2020), they are less likely to be bleached because the stratified water column suppresses turbulence and the sediments have no chance to be dispersed to the water surface. Moreover, thick benthic layer of fluid mud in the channel of Yangtze River mouth have been observed in the typhoon condition; numerical experiments indicate that the typhoon wind strongly enhances saltwater intrusion and therefore intensifies the degree of water stratification, leading to the formation and near-bed movement of the fluid mud layer from offshore region into the channel (Ge et al, 2018;.…”
Section: Reasons For Overestimation Of Osl Agesmentioning
confidence: 99%